2015
DOI: 10.1111/hex.12357
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing factual information with patient narratives in the cancer screening context: a qualitative study of acceptability and preferences

Abstract: ObjectiveTo explore people's responses to narrative information in the context of colorectal cancer screening.DesignNineteen in‐depth interviews were conducted with men and women (aged 45–59). Participants were given two types of colorectal screening information to read: factual and narrative. Participants gave their views on both types of information. Data were analysed using Framework Analysis.ResultsThe most frequent responses to the narrative information were that they were reassuring, made colorectal scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 22 publications
2
39
1
Order By: Relevance
“…Men passively acquired information in 13 studies: 4 quantitative, 2 qualitative, and 1 mixed‐methods study on prostate cancer screening; 3 qualitative studies and 1 quantitative study on colorectal cancer screening; 1 quantitative study on human papilloma virus and anorectal cancer prevention; and 1 qualitative study on general cancer information …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Men passively acquired information in 13 studies: 4 quantitative, 2 qualitative, and 1 mixed‐methods study on prostate cancer screening; 3 qualitative studies and 1 quantitative study on colorectal cancer screening; 1 quantitative study on human papilloma virus and anorectal cancer prevention; and 1 qualitative study on general cancer information …”
Section: Resultsmentioning
confidence: 99%
“…Four qualitative studies addressed facilitators to seeking colorectal cancer screening information . Bennett et al found that factual information about colorectal cancer made screening less abstract .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 15 included studies, one study used a qualitative design, two studies used a mixed methods design, and twelve studies used a quantitative design. Of these twelve studies, nine used a randomized (controlled) trial design.…”
Section: Resultsmentioning
confidence: 99%